Rethinking Zapotec time : cosmology, ritual, and resistance in colonial Mexico - Tavárez, David Eduardo (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture, 2022)
In 1702, after the brutal suppression of a Zapotec revolt, the bishop of Oaxaca proclaimed an amnesty for idolatry in exchange for collective confessions. To evade conflict, Northern Zapotec communities denounced ritual specialists and surrendered sacred songs and 102 divinatory manuals, which preserve cosmological accounts, exchanges with divine beings, and protocols of pre-Columbian origin that strongly resemble sections of the Codex Borgia. These texts were sent to Spain as evidence of failed Dominican evangelization efforts, and there they remained, in oblivion, until the 1960s. In this book, David Tavárez dives deep into this formidable archive of ritual and divinatory manuals, the largest calendar corpus in the colonial Americas, and emerges with a rich understanding of Indigenous social and cultural history, Mesoamerican theories of cosmos and time, and Zapotec ancestor worship. Drawing on his knowledge of Zapotec and Nahuatl, two decades of archival research, and a decade of fieldwork, Tavárez dissects Mesoamerican calendars as well as Native resistance and accommodation to the colonial conquest of time, while also addressing entangled transatlantic histories and shining new light on texts still connected to contemporary observances in Zapotec communities. -- Présentation de l'éditeur.